2020
DOI: 10.3390/nu12071903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Self-Efficacy and Motivation to Follow a Healthy Diet on Life Satisfaction of Patients with Cardiovascular Disease: A Longitudinal Study

Abstract: Today, cardiovascular disease has a great impact on the global population due to its high prevalence. One challenge that cardiovascular patients face to achieve a better prognosis is to follow a healthy diet. This study focused on psychological factors linked to adaptation to a healthy diet in these patients. The main objective was to analyze the interrelationship between motivation to follow a healthy diet and self-efficacy to adhere to the Mediterranean diet with life satisfaction over time. The sample consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…For instance, patients with improved self-efficacy were more probably to regularly exercise and engage in various programmes promoting physical activity. Additionally, such patients were also more probably to make better food choices (Castillo-Mayén et al, 2020). The findings of the present study showed considerable improvements in For instance, a quasi-experimental study evidenced that provision of nurse-led education and counselling prior to discharge, followed with two telephone follow-ups sessions, had no effect on the long-term self-efficacy of ACS patients in 3 and 12 months after discharge (Shim & Hwang, 2017).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…For instance, patients with improved self-efficacy were more probably to regularly exercise and engage in various programmes promoting physical activity. Additionally, such patients were also more probably to make better food choices (Castillo-Mayén et al, 2020). The findings of the present study showed considerable improvements in For instance, a quasi-experimental study evidenced that provision of nurse-led education and counselling prior to discharge, followed with two telephone follow-ups sessions, had no effect on the long-term self-efficacy of ACS patients in 3 and 12 months after discharge (Shim & Hwang, 2017).…”
Section: Discussionmentioning
confidence: 50%
“…For instance, patients with improved self‐efficacy were more probably to regularly exercise and engage in various programmes promoting physical activity. Additionally, such patients were also more probably to make better food choices (Castillo‐Mayén et al., 2020). The findings of the present study showed considerable improvements in short‐term perceived self‐efficacy to control symptoms and maintain function, and total cardiac self‐efficacy of participants in the intervention group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Improving self-efficacy is generally regarded as an essential intermediary factor in the effect of exercise interventions (Olander et al, 2013 ). Self-efficacy and autonomous motivation are the core psychological factors that affect the initiation and maintenance of healthy behaviors (Pelletier et al, 2017 ; Castillo-Mayen et al, 2020 ). In the present study, the TTM-based program was found to be an effective method for developing self-efficacy, resulting in regular exercise, a healthy diet, and positively enhanced health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on health behaviours have highlighted how confidence in one’s ability to perform a behaviour increases the likelihood they will enact it. 54 , 63 Those who are confident to change their menstrual products at university will therefore do so, reflecting reverse causation.…”
Section: Discussionmentioning
confidence: 99%